Global Governance in the New Era
XVI, 261 p. 13 illus., 4 illus. in color.
Keywords: This book mainly introduces the concepts and approaches of global governance from the viewpoints of Chinese and Russian scholars and is divided into four parts. The first one deals with the concept of a new type of global governance, namely “Globalization 2.0”. The second one is dedicated to institutions and multilateralism, including the importance and effectiveness of international institutions. The third part focuses on the important countries and regions in the new era, as well as such issues as the current global status quo, processes in Eurasia, the prospects of the U.S. – China – Russia trilateral relationship. The last part analyzes the future development of global governance and possible solutions of how it might be improved. Climate change, digital era, cyber security, financial and economic regimes, COVID-19 are all involved in this part. In short, this book is a profound and cutting-edge research on global governance.